A Comparison of Arch Index, Foot Posture Index and Surgeon Observation for Foot Type Classification. Issue 4 (22nd October 2020) - LaBaze, Dukens; Gabrielli, Alexandra; Anderst, William; Hogan, MaCalus V.
Category: Basic Sciences/Biologics Introduction/Purpose: Foot morphology is a key aspect of patient evaluation. Individuals with Pes planus usually have medial foot pain; those with Pes Cavus commonly have pain over lateral foot. Foot Posture Index (FPI) is a qualitative measure that uses six specific physical exam parameters. Arch index (AI) is a quantitative measure in which the footprint is photographed and measured. Radiographs allow for visualization of the bone and used to directly measure parameters of foot morphology such as calcaneal pitch (CP). The purpose of this study was to determine the sensitivity and specificity of surgeon observation, FPI, and AI in determining foot type, with CP serving as the reference standard. Our hypothesis is that surgeon observation will be more sensitive and specific than FPI and AI for identifying foot type. Methods: Following institutional review board approval and informed consent, we examined 41 adults (82 Feet) (average age 37.8+-17.6 yrs.; range: 20 to 68 years old; 20F/21M) without history of prior foot or ankle injury. Subject evaluation included bilateral FPI exam, lateral and hindfoot standing radiographs, pedographs, and weightbearing photographs. Three authors were trained to perform standardized FPI assessments. The radiographs and photographs were presented in a randomized order to a board-certified foot and ankle orthopaedic surgeon to classify a foot as either planus, cavus or normal (Figure 1). Calcaneal pitch was measured for each foot by finding the angle between the inferior surface of the calcaneus and the supporting surface, with normal classified as 18°-32°, planus <18° and, and cavus>32°[2, 3]. Arch index was calculated for each foot from pedograph, with normal classified as 0.21 to 0.28, planus < 0.21 and cavus >0.28. Results: The gold standard calcaneal pitch measurements identified 12 planus, 57 normal, and 13 cavus feet. Surgeon observation was the most sensitive for identifying planus feet and most specific for identifying cavus feet (Table 1). Arch index was the most sensitive for identifying cavus feet and most specific for identifying both planus and normal feet. FPI was most sensitive for identifying normal feet. The correlation between raw scores on the FPI and AI to CP were weak to moderate, -0.387 and -0.526, respectively (p<0.01). Conclusion: Surgeon observation is the only method that had a sensitivity over 0.50 for two different foot morphologies. FPI does not have the highest specificity for any particular foot type; however, a specificity of 0.844 and 0.971 for planus and cavus feet demonstrates that FPI is a suitable modality for evaluating pathologic morphology. Our specificity is close to a prior reported 0.932. These similarities in statistics reassure us that our methods are consistent with prior studies. Limitations of the study include small sample size and a single surgeon reviewing imaging.